A grassland strategy for farming systems in Europe to mitigate GHG emissions—An integrated spatially differentiated modelling approach. (15th December 2016) - Gocht, Alexander; Espinosa, Maria; Leip, Adrian; Lugato, Emanuele; Schroeder, Lilli Aline; Van Doorslaer, Benjamin; Paloma, Sergio Gomez y
Abstract: This paper assesses the impact of an EU-wide policy to expand grassland areas and promote carbon sequestration in soils. We use the economic Common Agricultural Policy Regionalized Impact (CAPRI) model, which represents EU agriculture using 2450 mathematical programming farm-type models in combination with the biogeochemistry CENTURY model, which provides carbon sequestration rates at a high resolution level. Both models are linked at the NUTS3 level using location information from the Farm Accounting Data Network. We simulated a flexible grassland premium such that farmers voluntary and cost efficiently increase grassland area by 5%. We find that the GHG mitigation potential and the costs depend on carbon sequestration rates, land markets and induced land use changes, and regional agricultural production structures. In Europe, the calculated net effect of converting 2.9 Mha into grassland is a reduction of 4.3 Mt CO2e (equivalents). The premium amounts to an average of EUR 238/ha, with a total cost of EUR 417 million for the whole EU. The net abatement costs are based on the premium payments, and account on average EUR 97/t CO2e. However, substantial carbon sequestration (28% of total sequestration) can be achieved at a rate of EUR 50/t CO2e. Carbon sequestration would be most effective in regions of France and Italy and in Spain, the Netherlands and Germany. Larger farms and farm-types specialized in 'cereals and protein crops', 'mixed field cropping' and 'mixed crop-livestock' farming systems have the highest mitigation potential at relatively low costs.